2007
DOI: 10.1109/iembs.2007.4352580
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Far-Infrared Therapy in Patients with Allergic Rhinitis

Abstract: Allergic rhinitis (AR) is the sixth most common chronic illness worldwide, which has a significant impact on patients' quality of life. The actual cost of AR is staggering, approximately $5.6 billion being spent annually in direct medical costs and other indirect costs. Therefore, it should be taken seriously upon its evaluation and treatment. AR is an IgE-mediated inflammation, which symptoms are likely due to increased vascular permeability. Current therapeutic options such as avoidance of allergen, medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Significant improvement in the symptoms of AR has also been claimed in one study after far infrared radiation (FIR) therapy [85]. FIR with an invisible electromagnetic wave of wavelength between 5.6 and 1000 μm is perceived as heat by thermo-receptors.…”
Section: Capsaicin Desensitization Complementary Alternative Treatmmentioning
confidence: 91%
“…Significant improvement in the symptoms of AR has also been claimed in one study after far infrared radiation (FIR) therapy [85]. FIR with an invisible electromagnetic wave of wavelength between 5.6 and 1000 μm is perceived as heat by thermo-receptors.…”
Section: Capsaicin Desensitization Complementary Alternative Treatmmentioning
confidence: 91%
“…This positive effect of thermal energy on the soft tissues has been demonstrated by Hu et al who have confirmed that local hyperthermia can also help to increase the microcirculatory blood flow, eliminate chronic inflammation, and promote tissue recovery. [34][35][36] We have demonstrated that the therapeutic effect on DLA in the HBT group is superior to that in the SBT group ( p < 0.05). This illustrates the therapeutic advantage that far infrared rays in combination with compression bandaging can have on DLA compared to SBT alone.…”
Section: Discussionmentioning
confidence: 82%
“…By applying FIR therapy to the nasal region in the patients with AR, our study demonstrated that FIR therapy could improve significantly for the clinical symptoms of eye itching, nasal itching, nasal stuffiness, rhinorrhea and sneezing during period of therapy (Hu & Li, 2007). Thirty-one patients with perennial AR enrolled in the study completed the FIR therapy.…”
Section: Far Infrared Irradiation In Allergic Rhinitismentioning
confidence: 85%